2017
DOI: 10.1109/lsp.2017.2748230
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Manifold Algorithm for Constructive Interference Based Constant Envelope Precoding

Abstract: In this letter, we propose a novel manifold-based algorithm to solve the constant envelope (CE) precoding problem with interference exploitation. For a given power budget, we design the precoded symbols subject to the CE constraints, such that the constructive effect of the multi-user interference (MUI) is maximized. While the objective for the original problem is non-differentiable on the complex plane, we consider the smooth approximation of its real representation, and map it onto a Riemannian manifold. By … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 24 publications
0
72
0
Order By: Relevance
“…Let us define the dual variable that associate with the three constraints in (26) as u, v, c respectively, where u i ≥ 0, v i ≥ 0, c m ≥ 0, ∀i, ∀m are the elements of the three dual vectors. The corresponding Lagrangian is given as (27) at the top of the next page. By the following definitions…”
Section: B the Dual Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us define the dual variable that associate with the three constraints in (26) as u, v, c respectively, where u i ≥ 0, v i ≥ 0, c m ≥ 0, ∀i, ∀m are the elements of the three dual vectors. The corresponding Lagrangian is given as (27) at the top of the next page. By the following definitions…”
Section: B the Dual Problemmentioning
confidence: 99%
“…Recent works [25], [26] showed that by rotating the destructive interference into constructive region using optimization techniques, the receive SINR target for each user was actually relaxed compared to the conventional SDR-based beamformer, thus a significant power saving was obtained. Given the significant advantage of the interference exploitation technique, it has been already applied to various research fields [27]- [33].…”
Section: Introductionmentioning
confidence: 99%
“…Starting from , we can minimize the overall interference (over all UEs k ) . Noting that | g k s k | 2 is a constant, minimizing kikfalse|boldgk1ptHsi|2 is equivalent to minimizing kKiKfalse|boldg1ptkHsi|2, and the MUI minimization problem can be rewritten as alignleftalign-1align-2minikgkHboldsi2align-1align-2s.t.boldskfalse‖22=Pk,k, where minik||boldg1ptkHsi2=min‖‖GHboldSnormalF2.…”
Section: Proposed Solutionmentioning
confidence: 99%
“…Starting from (19), we can minimize the overall interference (over all UEs k). [34][35][36] Noting that…”
Section: General Definitionsmentioning
confidence: 99%
“…All of the above drawbacks make fully-digital processing highly undesirable for a massive MIMO BS. Accordingly, there have been several emerging techniques that aim to reduce the hardware complexity and the power consumption for a massive MIMO BS, including hybrid analog-digital (AD) precoding [15]- [22], constant-envelope (CE) precoding [23]- [26], and low-resolution DACs.…”
mentioning
confidence: 99%